KURANGNYA PELAYANAN TERHADAP PASIEN BPJS SEBAGAI KONSUMEN KESEHATAN - Listy Fadilla Utami; Lilawati Ginting (Universitas Pahlawan Tuanku Tambusai, 2022)
The purpose of this writing is to discuss social inequalities that often occur in the health sphere, where the presence of the BPJS Kesehatan program is expected to provide good health services regardless of economic and social status, but in its implementation there are still often non-fulfillment of the rights of people who use BPJS Kesehatan. , even though Health BPJS is issued by the government to obtain health insurance as stipulated and contained in the Law of the Republic of Indonesia No. 40 of 2004 concerning the National Social Security System, it is organized nationally based on social insurance principles and equity principles with the aim of ensuring that participants or patients receive health care benefits and protection in meeting health needs. In principle, legal protection for BPJS Health participants is in accordance with the laws and regulations related to the BPJS Health program, but the implementation of legal protection is still ineffective. Analyzing the service problems in BPJS Health is still not providing good service to participants as BPJS Health patients. Keywords: legal protection, BPJS patients, services